Results of study of wild medicinal plants of Mangystau region - Imanbayeva, А.А.; Gassanova, G.G.; Tuyakova, А.Т. (Fundamental and Experimental Biology, 2020)
The study of medicinal plants in the flora of the Mangystau region was the practical interest in assessing the full species composition and prospects for the use of raw materials for the medical and pharmaceutical industries. During 2013–2020, field surveys were carried out to identify the species composition of medicinal plants, their ranking, raw materials and the characteristics of the passage of the main phases of vegetation. The article presents the results of the analysis of the species composition of wild medicinal plants in the natural conditions of Mangystau and their ranking. As a result, the list of medicinal plants amounted to 166 species from 112 genera and 43 families. The predominant number of species is assigned to the families Asteraceae, Chenopodiaceae, Fabaceae, Brassicaceae, Lamiaceae, Apiaceae, Scrophulariaceae, Boraginaceae, Euphorbiaceaeand Ranunculaceae. The largest part of medicinal plants is assigned to species used in folk medicine — 144 species; pharmacological properties were found for 50 species; 36 species are included in the Pharmacopoeia of the Republic of Kazakhstan. All plants species were ranked into 10 groups of pharmaceutical-therapeutic activity against different diseases: gastrointestinal tract, oral cavity, kidneys and urinary tract, respiratory tract, antipyretic and anti-inflammatory, cardiovascular system, diabetes mellitus, analgesic and wound healing, skin organs, other diseases. There was performed ranking of medicinal plant species into 4 groups by degree of distribution, area of thickets and possibility of stock collection of vegetal raw materials. A collection calendar has been compiled for 166 species of medicinal plants in the flo-ra of the Mangystau region. The obtained data can be used for organization of systematic harvesting of vege-tal raw materials and development of environmental measures.